Coastal Abrasion Vulnerability of the Southern Seluma Regency, Bengkulu, Based on Seismic Properties and Parameters Elasticity - Natasya, Indah Dwi; Refrizon, Refrizon; Hadi, Arif Ismul; Fadli, Darmawan Ikhlas; Larang, Miranda Puspa; Putri, Elona Gita Gatra; Maghribi, Faritz Bagda; Sumanjaya, Erlan (Indonesian Journal on Geoscience, 2025)
Geophysical investigations were conducted in the coastal area of Seluma Regency using Multi-Channel Analysis of Surface Waves (MASW) to determine subsurface geology, material stiffness, and potential weak zones to a depth of approximately 30 m. This study aims to identify and map the susceptible areas to abrasion in Seluma Regency coastal region and to analyze the causal factors associated with parameters elasticity of subsurface rocks. Data acquisition, processing, and inversion have been parameterized and selected to produce shear wave velocities representing actual subsurface conditions using Win-MASW 5.0 Professional software. The shear wave velocity analysis shows that the coastal area of Seluma Regency has the potential for high and moderate ground deformation which is vulnerable to abrasion. The area with high deformation potential is the Air Periukan Sub-Regency, Seluma Regency, Indonesia.